Adjuvant-independent airway sensitization and infection mouse models leading to allergic asthma - Radhouani, Mariem; Starkl, Philipp (Frontiers in Allergy, 2024)
Asthma is a chronic respiratory disease of global importance. Mouse models of allergic asthma have been instrumental in advancing research and novel therapeutic strategies for patients. The application of relevant allergens and physiological routes of exposure in such models has led to valuable insights into the complexities of asthma onset and development as well as key disease mechanisms. Furthermore, environmental microbial exposures and infections have been shown to play a fundamental part in asthma pathogenesis and alter disease outcome. In this review, we delve into physiological mouse models of allergic asthma and explore literature reports on most significant interplays between microbial infections and asthma development with relevance to human disease.